2014
DOI: 10.1128/aem.04049-13
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Metabolites Secreted by Paenibacillus larvae as Potential Virulence Factors of American Foulbrood

Abstract: The spore-forming bacterium Paenibacillus larvae causes a severe and highly infective bee disease, American foulbrood (AFB). Despite the large economic losses induced by AFB, the virulence factors produced by P. larvae are as yet unknown. To identify such virulence factors, we experimentally infected young, susceptible larvae of the honeybee, Apis mellifera carnica, with different P. larvae isolates. Honeybee larvae were reared in vitro in 24-well plates in the laboratory after isolation from the brood comb. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Based on larval feeding assays it has been suggested that low molecular weight metabolites present in P. larvae secretomes may possess larval toxicity although no further identification of the proposed cytotoxin was provided [43]. However, it was speculated that NRP or NRP/PK hybrid molecules are responsible for the observed effect [43].…”
Section: Identification and Role Of Cytotoxinsmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on larval feeding assays it has been suggested that low molecular weight metabolites present in P. larvae secretomes may possess larval toxicity although no further identification of the proposed cytotoxin was provided [43]. However, it was speculated that NRP or NRP/PK hybrid molecules are responsible for the observed effect [43].…”
Section: Identification and Role Of Cytotoxinsmentioning
confidence: 98%
“…In another study, the lipopeptides paenilarvins exhibited some larvicidal activity in feeding assays [32 ]. In both studies control groups did not receive any control peptides but were fed normal larval diet [32 ,43] and all secretome fractions were toxic to larvae [43]. Therefore, it cannot be ruled out that the observed larvicidal effects were just due to the added peptides per se rather than to a specific peptide because larvae are very sensitive to changes in the larval diet during artificial rearing [44].…”
Section: Identification and Role Of Cytotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third toxin, (C3 larvin) was identified via a bioinformatics strategy . Moreover, P. larvae produces further unidentified low molecular mass metabolites toxic for honeybee larvae .…”
Section: Introductionmentioning
confidence: 99%
“…; Schild et al. ) including an NRPS gene cluster leading to the production of a novel nonribosomal peptide antibiotic, sevadicin (Garcia‐Gonzalez et al. ).…”
Section: Introductionmentioning
confidence: 99%